Analisis Kemampuan Berpikir Reflektif Siswa SMP Berdasarkan Gaya Belajar - Nia Mentari; Hepsi Nindiasari; Aan Subhan Pamungkas (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2018)
The research is a qualitative descriptive research, the purpose of this research is to analyze students reflective thinking ability in terms of learning style. learning style in this research consists of three types namely visual, auditorial, and kinestetik. The subjects of the study were class VIII in one of the middle schools in Serang district selected by purposive sampling. Based on the analysis results obtained description of students' reflective mathematical thinking ability as follows: (1) Visual students have been able to provide interpretation but not yet complete and correct calculation; (2) Auditorial and kinesthetic students are able to provide correct interpretation and calculation. (3) In identifying the concept, visual students have been able to identify the formulas, auditorial and kinesthetic students have not been able to. (4) In evaluating/checking the validity of visual and auditorial students is already capable while kinestetik yet. (5) In distinguishing between relevant data visual and auditorial students have been able, and kinesthetic students have not been able. (6) In drawing the analogy of two cases, visual, auditorial, and kinesthetic students have not been able to. (7) In harmonizing with reason, visual, auditorial and kinesthetic students have not been able.